Microscopic approach to random walks - Zaburdaev, Vasily (Journal of Statistical Physics, 2008)
In the present paper the microscopic approach to random walk models is introduced. For any particular model it provides a rigorous way to derive the transport equations for the macroscopic density of walking particles. Although it is not more complicated than the standard random walk framework it has virtually no limitations with respect to the initial distribution of particles. As a consequence, the transport equations derived with this method almost automatically give answers to such important problems as aging and two point probability distribution. © 2008 Springer Science+Business Media, LLC.
Created from Fastlane, Scopus look-up
Keywords: Aging; Continuous time random walk model; Coupled random walks; Two-point probability function